Randomized, placebo‐controlled, double‐blind trial of clobetasol propionate 0.05% in the treatment of oral lichen planus. (13th March 2018) - Arduino, PG; Campolongo, MG; Sciannameo, V; Conrotto, D; Gambino, A; Cabras, M; Ricceri, F; Carossa, S; Broccoletti, R; Carbone, M
Abstract : Objective: To perform a randomized, placebo‐controlled, double‐blind study, with a follow‐up period of 6 months, for the use of topical clobetasol in cases of symptomatic oral lichen planus (OLP). Subjects and Methods: Thirty‐two participants were analyzed, with the aims of: (I) to compare the usefulness of topically applied clobetasol propionate 0.05% (mixed with 4% hydroxyethyl cellulose gel) and 4% hydroxyethyl cellulose gel alone (considered as placebo) in the management of OLP; (II) to describe which of them is quicker in decreasing signs and reported symptoms, and (III) which is able to give the proper longer remission in the follow‐up. Results: Symptoms improved in all clobetasol‐treated patients during the first 2 months of therapy, while only 50% of placebo control group ( p = .005) displayed similar results; of the remaining half, 12.5% did experienced a worsening while 37.5% remained stable. Regarding clinical signs, 87.5% of clobetasol‐treated patients improved, while only 62.5% of the placebo‐treated patients had a positive response ( p = .229). Conclusions: It is possible to report that clobetasol, at this dosage, has been more effective than a placebo at provoking symptoms improvement in subjects affected by atrophic‐erosive oral lesions.